Assessing Magnesium Chloride as a Chemical for Immobilization of a Symbiotic Jellyfish (Cassiopea sp.) - Silvia Arossa; Shannon G. Klein; Anieka J. Parry; Manuel Aranda; Carlos M. Duarte (Frontiers in Marine Science, 2022)
Immobilization of marine invertebrates for research purposes has been commonly used and is often necessary to obtain high-quality findings. Despite these approaches being standard procedures, they can affect the specimens, and their responses as well. The effectiveness of magnesium chloride (MgCl 2 ) to “narcotize” marine invertebrates has been recognized since 1946. Here, we determine the concentration of MgCl 2 that immobilizes Cassiopea sp., at jellyfish stage, effectively and quickly, without causing mortality. The specimens were exposed to different concentrations of MgCl 2 , until the range was narrowed, and the most effective concentration was found (0.092M). In the final experiment, the jellyfish (~ 8.68 cm ± 1.70 SD of diameter) were exposed to a 0.092M MgCl 2 solution for 2 and 24 hours. Before, during, and after the exposure we monitored the following biological responses: (1) cessation of bell pulsations, (2) responsiveness to bell-tap stimulus, (3) photochemical efficiency, (4) bell pulsation, (5) recovery time, and (6) survival after 24 and 48 hours from exposure. Environmental conditions (pH and dissolved oxygen, d O 2 ) were monitored as well. Our findings indicate that, despite being an effective concentration for immobilization of Cassiopea sp. at jellyfish stage, their bell pulsations were significantly affected both after 2 and 24 hours when comparing the values measured in the “pre-incubation” and “immediate post-incubation” phases, whereas bell size was significantly affected only in the 24 hours incubation. In conclusion, we suggest that this concentration can be used to immobilize Cassiopea sp.at jellyfish stage for short-term analyses. However, the limitations related to the use of this chemical should be reported, as it could lead scientists to misleading conclusions.